2000
DOI: 10.1530/eje.0.1420236
|View full text |Cite
|
Sign up to set email alerts
|

The role of cytokines and cortisol in the non-thyroidal illness syndrome following acute myocardial infarction

Abstract: Objective: A number of different hormone changes have been described during the acute myocardial infarction (AMI), including those of the non-thyroidal illness syndrome (NTIS). Design and methods:We assessed the alterations of serum thyroid hormones, cytokines and cortisol levels in 30 patients with a first episode of AMI 4, 24, 48 h and 10 days (240 h) after the onset of the chest pain and we investigated the possible relationship of these alterations with the severity of AMI. Results: Fifteen patients had le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…The finding of elevated TSH concentrations during the initial stages of critical illness is entirely compatible with studies in human critical care [16]. It is known in humans that cytokines such as interleukin-6 exerts an inhibitory effect on the hypothalamic-pituitary-thyroid axis [4,5]. Results of our study, when seen in combination with a recently performed pilot study showing a positive correlation of IL-6 with mortality in dogs admitted with systemic inflammatory response syndrome, may lend credence to this cytokine as being instrumental in the reduction in thyroid hormone concentrations seen in our dogs [17].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The finding of elevated TSH concentrations during the initial stages of critical illness is entirely compatible with studies in human critical care [16]. It is known in humans that cytokines such as interleukin-6 exerts an inhibitory effect on the hypothalamic-pituitary-thyroid axis [4,5]. Results of our study, when seen in combination with a recently performed pilot study showing a positive correlation of IL-6 with mortality in dogs admitted with systemic inflammatory response syndrome, may lend credence to this cytokine as being instrumental in the reduction in thyroid hormone concentrations seen in our dogs [17].…”
Section: Discussionsupporting
confidence: 77%
“…A large proportion of infected dogs has measurable serum concentrations of endotoxin, which is a potent mediator of the systemic inflammatory response through its stimulation of the release of pro-inflammatory cytokines such as tumour necrosis factor [3]. These and other cytokines such as interleukin-1 (IL-1) and interleukin-6 (IL-6) have been shown to suppress the pituitaryethyroidal axis in human critical illness [4,5]. Critical illness in humans is characterized by multiple and complex alterations in the thyroid axis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These changes, which were similar to those associated with NTIS, were an early event in our patients and they appeared at the same time as the significant increase in serum our cases since the first measurements were 24 hr after ZA infusion and the possibility that we may have missed earlier significant changes cannot be excluded. Studies have shown that after acute stress, for example after myocardial infarction, the decrease in T3 appears within 24 h after the heart attack and lasts until recovery [20]. In surgical stress the decline in T3 appears within 30 minutes of the beginning of the surgical procedure, before skin incision and thus is an early event, before the rise of IL-6 and TNF-α [21].…”
Section: Discussionmentioning
confidence: 99%
“…All samples from peripheral blood were obtained the morning after overnight fast and were stored at -70°C until assayed, apart from a 0.5 ml sample that was immediately used for cell culture and determination of lymphocyte blastogenesis. Serum-free thyroxine (FT 4 ) levels, free triiodothyronine (FT 3 ) and TSH were measured as previously described [9]. Twelve age-matched healthy volunteers (six male, six female) of 24-69 years of age (mean ± SD 45.1 ± 3.3 years) served as the control group.…”
Section: Subjects and Study Protocolmentioning
confidence: 99%